1972
DOI: 10.1677/joe.0.0530447
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Concentration in the Peripheral Plasma of Pregnant Goats

Abstract: Plasma progesterone concentration was measured by a competitive protein-binding method in serial samples of jugular venous blood from 21 pregnant goats, 11 with twin and 10 with single foetuses.Progesterone levels in twin pregnancies were significantly greater than in singletons. The mean progesterone concentration (ng/ml plasma) in the twin pregnancies was greatest during the 3rd month of gestation (10\m=.\7 \ m=+-\0\m=.\4 (s.e.m.)) and in the singletons during the 4th month (7\m=.\8 \ m=+-\ 0\m=.\2 (s.e.m.))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 20 publications
3
5
0
1
Order By: Relevance
“…The changes in maternal peripheral plasma concentrations of progesterone and oestrogens in the goats that gave birth normally at term in the present study resemble those observed by previous workers (Challis & Linzell, 1971;Irving, Jones & Knifton, 1972;Thorburn & Schneider, 1972 (Currie & Thorburn, 1974). This period encompasses the gestation lengths of the operated goats in the present study and it seems possible that the corpus luteum of pregnancy has a finite, albeit variable, lifespan, which, in the absence of a more positive mechanism, would eventually terminate pregnancy.…”
Section: Resultssupporting
confidence: 88%
“…The changes in maternal peripheral plasma concentrations of progesterone and oestrogens in the goats that gave birth normally at term in the present study resemble those observed by previous workers (Challis & Linzell, 1971;Irving, Jones & Knifton, 1972;Thorburn & Schneider, 1972 (Currie & Thorburn, 1974). This period encompasses the gestation lengths of the operated goats in the present study and it seems possible that the corpus luteum of pregnancy has a finite, albeit variable, lifespan, which, in the absence of a more positive mechanism, would eventually terminate pregnancy.…”
Section: Resultssupporting
confidence: 88%
“…In pregnant animals, mean progsterone concentrations were in the range of those found by Thorburn & Schneider (1972) and Irving et al (1972) but no elevation of progesterone concen¬ trations with the stage of gestation was noticed. As reported for the ewe with the bovine PSPB assay (Ruder et al, 1988), Day 24 was the first day at which mean PSPB concentrations were different in pregnant (Group 3) and non-pregnant animals from Group 1.…”
Section: Discussionmentioning
confidence: 57%
“…A gestação concordaram com Irving et al (1972), Jain et al (1980), Currie et al (1988), Kornalijnslijper et al (1997), Romero et al (1998), Engeland et al (1999), Sousa et al (1999) e Prina (2007 que relataram diminuição gradativa até próximo ao momento do parto, com queda acentuada no dia do parto e diferiu dos resultados de Manalu et al (1996) onde os valores antes do parto e no dia do parto mantiveram-se quase que inalterados. Lye et al (1996) relataram que em muitas espécies, o início do parto está associado com uma interrupção no estado de dominância da progesterona para uma maior influência do estradiol.…”
Section: Resultsunclassified